Do Active Learning Models Differ? Examining of PBL, Cooperative Learning and Critical Thinking on Social Studies Outcomes - Sampurna, Iman; Muhyidin, Asep; Nulhakim, Lukman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study ams to analyse variations in students’ learning outcomes based on the learning models employed Problem-Based Learning (PBL) and Cooperative Learning and their levels of critical thinking. Method: This study employed a quasi-experimental approach with a 2 × 3 factorial design to examine the effects of instructional models and students’ critical thinking levels on learning outcomes. A total of 100 students participated in the study, with 50 students assigned to each instructional group. The participants were proportionally assigned to the groups using cluster random sampling. Results: The study produced three man findings: (1) there were differences in learning outcomes between students taught using PBL and those taught using Cooperative Learning; (2) learning outcomes varied among students with high, moderate, and low levels of critical thinking; and (3) there was an interaction effect between the instructional models and students’ critical thinking levels on their learning outcomes. Novelty: This study makes several important contributions to the existing literature. First, it directly compares two prominent active learning models, namely PBL and Cooperative Learning, within the same analytical framework rather than examining them separately. Second, it positions critical thinking not merely as an independent predictor of achievement but as a moderating variable that may influence the effectiveness of instructional models in improving social studies learning outcomes. Third, the study employs a factorial design that enables the simultaneous examination of both man and interaction effects. This approach provides a more comprehensive explanation of the relationship between learner characteristics and instructional models and contributes to the development of constructivist and social cognitive perspectives in social studies instruction.